Isolation and Identification of Volatile Components in Tempe by Simultaneous Distillation-Extraction Method by Modified Extraction Method - Syahrial Syahrial; M. Muchalal (Universitas Gadjah Mada, 2001)
An isolation and identification of volatile components in temps for 2, 5 and 8 days fermentation by simultaneous distillation-extraction method was carried out. Simultaneous distillation-extraction apparatus was modified by Muchalal from the basic Likens-Nickerson's design. Steam distillation and benzena as an extraction solvent was used in this system. The isolation was continuously carried out for 3 hours which maximum water temperature In the Liebig condenser was 8 °C. The extract was concentrated by freeze concentration method, and the volatile components were analyzed and identified by combined gas chromatography-mass spectrophotometry (GC-MS). The Muchalal's simultaneous distillation extraction apparatus have some disadvantage in cold finger condenser, and it's extractor did not have condenser. At least 47, 13 and 5 volatile components were found in 2, 5 and 8 days fermentation, respectively. The volatile components in the 2 days fermentation were nonalal, ɑ-pinene, 2,4-decadienal, 5-phenyldecane, 5-phenylundecane, 4-phenylundecane, 5-phenyldodecane, 4-phenyldodecane, 3-phenyldodecane, 2-phenyldodecane, 5-phenyltridecane, and caryophyllene; in the 5 days fermentation were nonalal, caryophyllene, 4-phenylundecane, 5-phenyldodecane, 4-phenyldodecane, 3-phenyldodecane, 2-phenyldodecane; and in the 8 days fermentation were ethenyl butanoic, 2-methy1-3-(methylethenyl)ciclohexyl etanoic and 3,7-dimethyl-5-octenyl etanoic.